A silk fibroin-based flexible neural electrode device for brain-computer interface

By using a silk fibroin substrate and a PEDOT:PSS/CNFs conductive layer in the brain-computer interface neural electrode, combined with a tannin-modified silk fibroin encapsulation layer, the problem of poor conformity and adhesion between nerve electrodes and brain tissue in the prior art is solved, and a high flexibility, excellent biocompatibility and degradable neural electrodes are achieved, which improves the stability and accuracy of signal monitoring.

CN119064432BActive Publication Date: 2025-04-18DONGHUA UNIV
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411555372.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-04
Publication Date
2025-04-18
Estimated Expiration
2044-11-04

AI Technical Summary

Technical Problem

The existing neural electrodes for brain-computer interfaces have problems with poor conformity or adhesion with brain tissue, resulting in poor stability and low accuracy of signal monitoring, and the base material is not degradable, which requires a secondary surgery to cause tissue damage.

Method used

Using a silk fibroin-based flexible neural electrode device, the ion selective electrode and reference electrode are integrated on the silk fibroin substrate, combined with the PEDOT:PSS/CNFs conductive layer and the tannin-modified silk fibroin encapsulation layer, the flexibility and biocompatibility of the electrode are improved, and the Young's modulus of the silk fibroin film is regulated by the gradient heating method.

Benefits of technology

High flexibility, excellent biocompatibility and degradable neural electrodes are achieved, which improves the stability and accuracy of signal monitoring, reduces damage to brain tissue, and enhances the adhesion performance between electrodes and tissues.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119064432B_ABST
    Figure CN119064432B_ABST
Patent Text Reader

Abstract

The present invention relates to a silk fibroin-based flexible neural electrode device for brain-computer interface, on which an ion selective electrode and a reference electrode are integrated, wherein the ion selective electrode comprises a silk fibroin substrate, a PEDOT:PSS / CNFs conductive layer, an ion selective membrane and a silk fibroin encapsulation layer; the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer are interspersed and fixed between the silk fibroin molecular chains on the silk fibroin substrate; the reference electrode comprises a silk fibroin substrate, an Ag / AgCl conductive layer, a PVB film and a silk fibroin encapsulation layer; the silk fibroin substrate is a silk fibroin film, and the silk fibroin encapsulation layer is a tannic acid-modified silk fibroin film; the Young's modulus of the silk fibroin film is below 10MPa. The product of the present invention can more effectively monitor the neural electrical signals and ion signals of the corresponding tissue, and can maximize the precision and accuracy of the detection.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of biosensors and relates to a silk fibroin-based flexible neural electrode device for a brain-computer interface. Background Art

[0002] Silk is composed of fibroin and sericin wrapped around it. Fibroin has excellent biocompatibility and mechanical flexibility, and is a potential natural polymer material suitable for manufacturing bioflexible electronic devices and biomedical materials. Effectively compounding regenerated silk fibroin with other metals or conductive polymers can improve its electrical signal conduction or sensing performance, thus being applied in the field of neuroelectrophysiological analysis. However, due to the non-specific response of conductive polymers and metals to ions, it is impossible to monitor and analyze potential changes related to specific ions.

[0003] So far, the technologies used to qualitatively or quantitatively detect changes in substances mainly include: fluorescence imaging technology and electrochemical methods. Fluorescence imaging technology uses dyes or protein probes with fluorescent properties combined with the substance to be tested to qualitatively analyze the changes in the substance by observing the fluorescence intensity. For example, the more mature calcium flow imaging can qualitatively track the changes in calcium ions in cells, but this solution can only monitor the changes in calcium ions at present, and the tracking technology for other important ions cannot be performed.

[0004] The electrochemical method is a real-time, dynamic sampling technology for studying neurochemical substances in the extracellular fluid of brain cells. With the help of a composite ion-selective film on the surface of the conductive layer, the screening and response functions of specific ions can be realized. By integrating ion-selective electrodes on neural electrodes, it is expected to simultaneously achieve quantitative recording of cortical electrophysiological signals and ion signals.

[0005] For example, patent CN202211202288.1 discloses an all-solid-state ion-selective electrode for detecting changes in trace ion concentrations in a solution. The electrode has multiple detection sites, achieving the purpose of microelectrode integration. Further verification shows that it can achieve accurate detection of potassium ions, but it uses a hard metal electrode as a substrate with poor flexibility, so it cannot be successfully applied to the detection of neural electrical signals.

[0006] Reference 1 (Angew. Chem. Int. Ed. 2020, 59, 10426-10430) reports an electrochemical array that can simultaneously identify multiple ion signals. The array is made of poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid (PEDOT) as a solid transduction layer, PEDOT is electrochemically deposited on a tungsten wire microelectrode array, and coated with a specific ion-selective film. The report shows that the electrode can successfully detect changes in neurochemical substances in mice in an epileptic state and can detect changes in pH in the cortex. However, tungsten wire electrodes are a type of invasive electrode that requires invading brain tissue to test the peak potential of cells, causing greater damage to brain tissue.

[0007] Reference 2 (Adv. Funct. Mater. 2022, 32, 2204794) prepared an ion-selective electrocortical electroencephalogram (ECoG) electrode with PDMS (polydimethylsiloxane) as the substrate and a carbon nanotube array as the transduction layer. This electrode can detect multiple neurochemical substances simultaneously, but the tissue adhesion of the PDMS material itself is poor, and it is easy to move or even slip on the tissue during testing, and there is still much room for improvement in measurement accuracy. In addition, the PDMS material cannot be degraded, and the secondary surgery that cannot be avoided during use will also cause great damage to the tissue.

[0008] In summary, existing neural electrodes for brain-computer interfaces, including a small number of neural electrodes that have both neural electrical signal and ion signal monitoring functions, all have problems with poor conformality or adhesion to brain tissue, which leads to poor stability and low accuracy of signal monitoring. In addition, the electrode substrates reported in the literature are all non-degradable materials, which need to be removed after signal monitoring, resulting in secondary surgical injuries.

[0009] Therefore, it is of great significance to study a degradable silk fibroin-based flexible neural electrode device for brain-computer interface to solve the problems existing in the prior art. Summary of the invention

[0010] The purpose of the present invention is to solve the problems existing in the prior art and provide a silk fibroin-based flexible neural electrode device for brain-computer interface.

[0011] To achieve the above object, the technical solution adopted by the present invention is as follows:

[0012] A silk fibroin-based flexible neural electrode device for brain-computer interface, wherein an ion-selective electrode and a reference electrode are integrated on the silk fibroin-based flexible neural electrode device, wherein the ion-selective electrode comprises a silk fibroin substrate, a PEDOT:PSS / CNFs (poly(3,4-ethylenedioxythiophene)-polystyrene sulfonic acid / carbon nanofiber) conductive layer, an ion-selective membrane and a silk fibroin encapsulation layer, wherein the silk fibroin substrate, the PEDOT:PSS / CNFs conductive layer and the ion-selective membrane are arranged from bottom to top;

[0013] The PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer are interspersed and fixed between the silk fibroin molecular chains on the silk fibroin substrate;

[0014] The reference electrode includes a silk fibroin substrate, an Ag / AgCl conductive layer, a PVB film and a silk fibroin encapsulation layer, and the silk fibroin substrate, the Ag / AgCl conductive layer and the PVB film are arranged from bottom to top;

[0015] Only specific ions can pass through the ion-selective film. Therefore, the ion-selective electrode integrated on the silk fibroin-based flexible neural electrode device can transmit neural electrical signals caused by changes in specific ion concentrations. The reference electrode is an electrode whose potential does not change with the environment. It forms a circuit with the ion-selective electrode and serves as a reference to measure the potential difference of the ion-selective electrode. The Ag / AgCl conductive layer and the PVB stabilizing film layer on it constitute the reference electrode. The requirement of the reference electrode is that the potential remains basically unchanged in an environment with various ion concentrations. Ag / AgCl can maintain a certain potential stability. The role of the PVB film is to maintain the chloride ion concentration around the electrode for a period of time, making the potential of the Ag / AgCl electrode more stable.

[0016] The silk fibroin substrate is a silk fibroin film, and the silk fibroin encapsulation layer is a tannic acid-modified silk fibroin film;

[0017] The Young's modulus of silk fibroin film is below 10MPa; Young's modulus can be used to characterize the flexibility of silk fibroin film. Young's modulus is the ratio of stress to strain when the film is stretched. The lower the Young's modulus, the smaller the stress generated when the material is subjected to a certain amount of deformation, that is, the smaller the rigidity and the higher the flexibility. The higher the flexibility of the silk fibroin substrate, the better the conformality of the electrode to the substrate, and the less damage the electrode will cause to the brain, which is helpful for long-term detection of the electrode.

[0018] As the preferred technical solution:

[0019] As described above, in a silk fibroin-based flexible neural electrode device for brain-computer interface, the thickness of the silk fibroin substrate in the ion-selective electrode and the reference electrode is 20~40μm, the thickness of the PEDOT:PSS / CNFs conductive layer is 10~20μm, the thickness of the ion-selective membrane is 10~20μm, the thickness of the Ag / AgCl conductive layer is 20~40μm, the thickness of the PVB film is 10~20μm, and the thickness of the silk fibroin encapsulation layer is 20~40μm.

[0020] The steps for preparing the ion-selective electrode of the silk fibroin-based flexible neural electrode device for brain-computer interface as described above are as follows:

[0021] (1) First, the silkworm cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions to cause calcium ion precipitation, and the calcium sulfate precipitate is removed by centrifugation to obtain a silk fibroin solution containing sodium ions;

[0022] (2) After mixing the PEDOT:PSS solution with CNFs, mechanical stirring was performed at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution;

[0023] (3) Printing the PEDOT:PSS / CNFs mixture onto a silicon wafer using piezoelectric drop-on-demand inkjet printing technology to obtain a silicon wafer with a PEDOT:PSS / CNFs pattern printed on it;

[0024] (4) 0.5-1 mL of silk fibroin solution was cast onto a silicon wafer with an inkjet-printed PEDOT:PSS / CNFs pattern by a tape-casting method, and the silk fibroin solution was solidified by heating with a gradient heating method. After the silk fibroin solution containing sodium ions was solidified, it was placed at 4°C for 24 h to fix the crystalline structure inside the silk fibroin, and then the silicon wafer was detached, which was equivalent to transferring PEDOT:PSS / CNFs from the silicon wafer to the silk fibroin substrate, that is, forming a PEDOT:PSS / CNFs conductive layer on the silk fibroin substrate.

[0025] (5) The ion-selective precursor solution was adjusted to 1~6 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a target ion solution with a concentration of 0.1 mol / L for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer;

[0026] (6) Casting 0.5-1 mL of the silk fibroin solution on a silicon wafer by a tape casting method, and solidifying the silk fibroin solution by heating it by a gradient heating method; after the silk fibroin solution containing sodium ions is solidified, the silicon wafer and the silk fibroin film are separated, and the contact site is cut out on the silk fibroin film by a blade, and the contact site is attached to the surface of the device prepared by steps (1) to (5) (except for the contact site);

[0027] (7) Spin-coat a tannic acid solution with a mass fraction of 2 to 8% onto the surface of the silk fibroin film in step (6) and place it at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer.

[0028] Silk fibroin film consists of two parts: crystalline region and amorphous region. The ratio and distribution of the two are closely related to the mechanical properties of the film. Generally speaking, the crystalline region can improve the strength and stiffness of the silk fibroin film, while the amorphous region can improve the elasticity and flexibility of the film.

[0029] When the silk fibroin solution is directly heated at a continuous "high temperature", the molecular chains of the silk fibroin will move violently faster, and it is easy to form a large number of β-folded structures in a short time, so that the film has strong rigidity. However, during the gradient heating process, the molecular chains of the silk fibroin will move and rearrange relatively gently during the early "low temperature" heating, and then the β-folded structure can be formed relatively slowly. In addition, it can be foreseen that due to the volatilization of some solvents during the early "low temperature" heating and the formation of some β-folded structures in the system, the molecular chain movement during the later "high temperature" heating will be hindered to a certain extent, thus causing the crystalline structure content formed during the gradient heating process to be lower than that of the direct "high temperature" heating. In addition, the distribution of the β-folded structure formed during the gradient heating process will also be more uniform, thereby comprehensively ensuring that the gradient heating silk fibroin film has better flexibility and structural stability. The Young's modulus of the silk fibroin film formed by continuous high temperature heating is between 15 and 20 MPa, and the Young's modulus of the silk fibroin film is reduced to below 10 MPa by step-like temperature increase in the present invention.

[0030] The present invention uses a heat-assisted method to tightly combine the silk fibroin substrate with the PEDOT:PSS conductive layer, and the specific method is to cast the regenerated silk fibroin solution onto the PEDOT:PSS conductive electrode array. At the beginning, the silk fibroin molecular chains in the solution are relatively loose, which is conducive to the insertion of the PEDOT:PSS molecular chains between the silk fibroin molecular chains; during the further volatilization of the solvent, the molecular chains of the silk fibroin film gradually become dense, so that the PEDOT:PSS molecular chains are inserted between the silk fibroin chains to form a firm intercalation interlocking structure, thereby ensuring the firm combination of the conductive polymer array and the silk fibroin electrode substrate. At the same time, the metal salt ions in the silk fibroin solution can be doped into the PEDOT:PSS molecules during the heating process, thereby improving the hole transport capacity of the PEDOT:PSS, and thus can also improve the conductivity of the PEDOT:PSS conductive layer. The better the conductivity, the higher the sensitivity of the measured neural electrical signals and ion signals, that is, the electrical signals caused by more subtle neural activities can be measured.

[0031] In the silk fibroin-based flexible neural electrode device as described above, the ratio of the formic acid / calcium chloride mixture to the degummed silk fiber in step (1) is 12 mL:1 g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution containing sodium ions, the concentration of silk fibroin is 7-8 wt%, and the concentration of sodium ions is 3.5-4 wt%.

[0032] In the silk fibroin-based flexible neural electrode device as described above, the ratio of the amount of PEDOT:PSS solution to CNFs in step (2) is 1 mL:3 g, and the concentration of the PEDOT:PSS solution is 12 mg / mL.

[0033] In the silk fibroin-based flexible neural electrode device as described above, the piezoelectric inkjet on-demand inkjet printing technology in step (3) uses a sinusoidal piezoelectric pulse with a vibration frequency of 250 Hz, an amplitude of 30 V, and a pulse period of 20 s; the heating temperature of the substrate during printing is 35°C so that the ink can quickly form a printed layer; and the nozzle diameter used for printing is 80 μm.

[0034] In the silk fibroin-based flexible neural electrode device as described above, in step (4) and step (6), the gradient heating method is specifically: heating at 40°C for 10-15 min, 50°C for 10-15 min, 60°C for 5-10 min and 70°C for 5-10 min.

[0035] A silk fibroin-based flexible neural electrode device as described above, wherein the ion-selective precursor solution in step (5) is a potassium ion selective permeable solution, a calcium ion selective permeable solution or a sodium ion selective permeable solution, and the target ion solution is a potassium ion solution, a calcium ion solution or a sodium ion solution;

[0036] The potassium ion selective permeable solution is obtained by dissolving polyvinyl chloride (PVC), diisooctyl sebacate (DOS), sodium 4[3,5-bis(trifluoromethyl)phenyl]borate (NaTFPB) and valinomycin in tetrahydrofuran; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin, the proportion of polyvinyl chloride is 64-66wt%, the proportion of diisooctyl sebacate is 32-33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5-1wt%, and the proportion of valinomycin is 1-2wt%;

[0037] The calcium ion selective permeable solution is obtained by dissolving polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II in tetrahydrofuran; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II, the proportion of polyvinyl chloride is 64-66wt%, the proportion of diisooctyl sebacate is 32-33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5-1wt%, and the proportion of calcium ion carrier II is 1-2wt%;

[0038] The sodium ion selective permeable solution is obtained by dissolving polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X in tetrahydrofuran; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X, the proportion of polyvinyl chloride is 64-66wt%, the proportion of diisooctyl sebacate is 32-33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5-1wt%, and the proportion of sodium ion carrier X is 1-2wt%.

[0039] The preparation process of the reference electrode is roughly the same as that of the ion-selective electrode, except that: ① the Ag / AgCl conductive layer is prepared on the silk fibroin substrate. Specifically, the Ag / AgCl mixed paste (the mass ratio of Ag to AgCl is 1:1) is printed on the silk fibroin substrate using screen printing technology, and then applied 2 to 3 times continuously and cured at 60°C for 3 hours; ② the PVB (polyvinyl butyral) film precursor solution is prepared at a rate of 1 to 6 μL / mm 2The PVB film precursor solution was prepared by dropping it on the contact site surface of the Ag / AgCl conductive layer and leaving it for 24 hours to allow the solvent to completely evaporate, thereby forming a PVB film on the surface of the Ag / AgCl conductive layer. The preparation process of the PVB film precursor solution was as follows: PVB powder (manufacturer: Aladdin, brand: P294391) was dissolved in a methanol solution (the mass ratio of methanol to PVB was 9:1), and mechanically stirred at 300 rpm for 120 minutes; after the solution was completely dissolved, sodium chloride and silver nitrate were added to the PVB solution (the ratio of the amount of PVB solution, sodium chloride and silver nitrate was 1 ml: 50 mg: 50 mg), and mechanically stirred at 500 rpm for 30 minutes to prepare Ag / AgCl. + The white suspension is the PVB film precursor solution.

[0040] As described above, a silk fibroin-based flexible neural electrode device for brain-computer interface is also integrated with conventional electrodes. The conventional electrodes are different from ion-selective electrodes only in that there is no ion-selective membrane, that is, the conventional electrodes include a silk fibroin substrate, a PEDOT:PSS / CNFs conductive layer and a silk fibroin encapsulation layer. Through the conventional electrodes integrated on the silk fibroin-based flexible neural electrode device, the conductive layer can transmit neural electrical signals caused by changes in various ion concentrations during neural activity.

[0041] Principle of the invention:

[0042] Natural silk has excellent flexibility and unique and ordered multi-level aggregate structure, which provides important raw materials and technical references for the development of biomass-based flexible materials. In the present invention, the substrate material and encapsulation layer of the electrode are both silk fibroin films. Based on the regulation of the silk fibroin film formed by programmed temperature control, the amorphous and crystalline compositions in the film can be well regulated, thereby giving the film a lower Young's modulus and good flexibility, which ensures the excellent flexibility of the electrode substrate and the encapsulation layer. In addition, the conductive layer used in the present invention is also a conductive polymer material with excellent flexibility, thereby comprehensively ensuring the good flexibility of the entire electrode device and the conformality of brain tissue.

[0043] At the same time, in order to further increase the close contact between the electrode and the tissue, and thus maximize the detection sensitivity of the electrode to the microenvironmental signal. The present invention also uses tannic acid to modify the surface of the encapsulation layer (tissue contact surface) of the silk fibroin film. Tannic acid is extracted from plants and is a slightly acidic polyphenolic substance. It contains a large number of gallic groups, which can form hydrogen bonds with groups such as hydroxyl (-OH) on the surface of biological tissues, thereby improving the adhesion performance of the material on the tissue surface. The gallic group is composed of three adjacent -OH groups connected to a benzene ring, so each gallic group can be a site for forming hydrogen bonds. In the preparation process of the silk fibroin-tannic acid tissue adhesion layer, when tannic acid contacts the silk fibroin film, the carboxyl and hydroxyl groups on the silk fibroin molecules can easily interact with the hydroxyl groups on the tannic acid, thereby achieving the interface composite of the silk fibroin film and tannic acid, and forming a silk fibroin-tannic acid adhesion gel layer. In addition, there are still a large number of hydroxyl groups on the surface of the tannic acid gel layer that have not formed hydrogen bonds. Therefore, when the electrode contacts the cerebral cortex, these hydroxyl groups can form hydrogen bonds with the cerebral cortex tissue, thereby achieving a good adhesion effect with the tissue. This further ensures the excellent conformal contact effect between the electrode and the brain tissue, thereby maximizing the sensitivity of the electrode to related signals.

[0044] Regarding the bonding problem between the conductive polymer layer and the silk fibroin electrode substrate, the present invention forms a strong intercalation interlocking structure by intercalating and fixing the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer between the silk fibroin molecular chains on the silk fibroin substrate, thereby ensuring the strong bonding between the conductive polymer array and the silk fibroin electrode substrate. The strong bonding between the conductive layer and the substrate is an important basic requirement for neural electrodes, which can ensure that the conductive layer will not fall off the substrate during the test process, so as to ensure the stability of signal monitoring and the reliability of long-term monitoring.

[0045] Beneficial effects:

[0046] (1) The silk fibroin-based flexible neural electrode device for brain-computer interface of the present invention uses silk fibroin with comprehensive advantages such as high flexibility, excellent biocompatibility, and complete in vivo degradation to construct the electrode substrate, and at the same time firmly combines the conductive polymer array with excellent flexibility, so that it has good flexibility and excellent common contact effect; and further compounded with a film with specific ion recognition function, successfully prepared a silk fibroin-based flexible neural electrode with both neural electrical signal and ion signal monitoring functions;

[0047] (2) The silk fibroin-based flexible neural electrode device for brain-computer interface of the present invention has good biological tissue adhesion function based on the interface modification of the silk fibroin electrode packaging layer, which can more effectively monitor the neural electrical signals and ion signals of the corresponding tissues, and maximize the detection precision and accuracy of the electrodes for neural electrical signals and ion signals;

[0048] (3) The silk fibroin-based flexible neural electrode device for brain-computer interface of the present invention has the function of monitoring both neural electrical signals and microenvironment-specific ion signals, which is conducive to a more systematic and comprehensive understanding of the electrophysiological signal conditions in the process of neurological diseases;

[0049] (4) The present invention is a silk fibroin-based flexible neural electrode device for brain-computer interface, wherein the substrate and encapsulation layer used for the neural electrode are both silk fibroin with excellent biocompatibility. The material can be completely degraded and absorbed by the body in vivo; after the monitoring is completed, the electrode can remain in the body to be degraded and absorbed, thereby avoiding adverse effects such as secondary surgical injuries. BRIEF DESCRIPTION OF THE DRAWINGS

[0050] Figure 1 A top view of a silk fibroin-based flexible neural electrode device for brain-computer interface;

[0051] Figure 2 is a cross-sectional view of an ion selective electrode;

[0052] Figure 3 is a cross-sectional view of the reference electrode;

[0053] Figure 4 It is a cross-sectional view of a conventional electrode;

[0054] Figure 5 This is a cross-sectional SEM image of the structure of the silk fibroin film and the PEDOT / CNFs conductive layer in Example 1;

[0055] Figure 6 This is the working principle diagram of potassium ion selective electrode;

[0056] Figure 7 1 is the stress-strain curve of the silk fibroin film substrate of Comparative Example 2 and Example 1;

[0057] Figure 8 is the Young's modulus of the silk fibroin film substrate of Comparative Example 2 and Example 1;

[0058] Fig. 9 is the sensitivity curve of the potassium ion selective electrode of Example 1;

[0059] Fig.10 is the sensitivity calibration curve of the potassium ion selective electrode of Example 1;

[0060] Fig.11 is the sensitivity curve of the sodium ion selective electrode of Example 2;

[0061] Fig.12 is the sensitivity calibration curve of the sodium ion selective electrode of Example 2;

[0062] Fig.13 is the sensitivity curve of the calcium ion selective electrode of Example 3;

[0063] Fig.14 is the sensitivity calibration curve of the calcium ion selective electrode of Example 3;

[0064] Fig.15 The long-term stability test results of the potassium ion selective electrode of Example 1;

[0065] Fig.16 The long-term stability test results of the calcium ion selective electrode of Example 2;

[0066] Fig.17 The long-term stability test result of the sodium ion selective electrode of Example 3;

[0067] Fig.18 This is a photo of a silk fibroin-based flexible neural electrode on a brain model;

[0068] Among them, 1-conventional electrode, 2-ion selective electrode, 3-reference electrode, 4-PEDOT:PSS / CNFs conductive layer, 5-Ag / AgCl conductive layer, 6-silk fibroin substrate, 7-ion selective membrane, 8-silk fibroin encapsulation layer, 9-PVB film. DETAILED DESCRIPTION

[0069] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.

[0070] The test methods involved in the performance indicators in the embodiments and comparative examples of the present invention are as follows:

[0071] Young's modulus: The sample was tensile tested using an electronic universal strength tester (Instron 5565, USA), wherein the sample was cut into a 5 mm × 20 mm rectangle using a knife, the maximum load of the tester sensor was 5 N, the chuck distance was 2 cm, the tensile rate was 2 mm / min, the test environment was 20 ± 5 ° C, the relative humidity was 60%, and the stress / strain ratio at the strain of 0.5% was taken as the sample Young's modulus; each group of samples was tested three times in parallel and the average value was taken.

[0072] Sensitivity characterization: Use a stainless steel electrode clip to fix the electrode contact and immerse it in deionized water; use an ion-selective electrode as the working electrode, and a silver chloride electrode as the reference electrode and counter electrode to form a two-electrode system. Connect the two electrodes to an electrochemical workstation (PGSTAT 204, the Netherlands), and use an open circuit voltage-time program to test the sensitivity of the material; after baseline equilibrium, add a certain volume of target ion solution with a known concentration to the electrolytic cell at the same interval (50s), and record the change of electrode potential over time.

[0073] Sources of some substances of the present invention:

[0074] PEDOT:PSS: Manufacturer: Heraeus, Germany, Brand: PH1000;

[0075] PVB powder: Manufacturer: Aladdin, Brand: P294391;

[0076] Polyvinyl chloride: Manufacturer: Sigma-Aldrich, brand number: 346764.

[0077] Example 1

[0078] A silk fibroin-based flexible neural electrode device for brain-computer interface, the preparation steps of which are as follows:

[0079] (1) Preparation of ion selective electrodes;

[0080] (1.1) First, the silkworm cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution is obtained;

[0081] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution containing sodium ions, the concentration of silk fibroin is 7wt%, and the concentration of sodium ions is 3.5wt%;

[0082] (1.2) PEDOT:PSS solution with a concentration of 12 mg / mL was mixed with CNFs at a ratio of 1 mL:3 g, and then mechanically stirred at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution;

[0083] (1.3) Printing the PEDOT:PSS / CNFs mixture onto a silicon wafer using a piezoelectric drop-on-demand inkjet printing technique to obtain a silicon wafer with a PEDOT:PSS / CNFs pattern printed thereon;

[0084] Among them, the inkjet piezoelectric drop-on-demand inkjet printing technology uses a sinusoidal piezoelectric pulse with a vibration frequency of 250Hz, an amplitude of 30V, and a pulse period of 20s; the heating temperature of the substrate during printing is 35°C; the nozzle diameter used for printing is 80μm;

[0085] (1.4) 0.5 mL of a silk fibroin solution containing sodium ions was cast onto a silicon wafer having an inkjet-printed PEDOT:PSS / CNFs pattern by using a tape-casting method, and the silk fibroin solution containing sodium ions was solidified by heating it using a gradient heating method; after the silk fibroin solution containing sodium ions was solidified, it was placed at 4°C for 24 h, and then the silicon wafer was detached, thereby forming a PEDOT:PSS / CNFs conductive layer on the silk fibroin substrate; the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer were interlaced and fixed between the silk fibroin molecular chains on the silk fibroin substrate;

[0086] The gradient heating method is as follows: heating at 40°C for 10 min, 50°C for 10 min, 60°C for 10 min and 70°C for 10 min in sequence;

[0087] like Figure 5 Shown is a cross-sectional scanning electron microscope image of the silk fibroin film and the PEDOT / CNFs conductive layer structure. There is a transition layer between the silk fibroin base layer and the PEDOT / CNFs conductive layer. In the transition layer, the silk fibroin and the conductive polymer PEDOT form an intercalated interlocking structure of molecular chains. Therefore, the PEDOT / CNFs conductive layer can be firmly fixed on the silk fibroin film base.

[0088] (1.5) Dissolve polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin in tetrahydrofuran to obtain a potassium ion selective permeable solution with a concentration of 5.3wt%; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin, the proportion of polyvinyl chloride is 65wt%, the proportion of diisooctyl sebacate is 32wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 1wt%, and the proportion of valinomycin is 2wt%; the ratio of tetrahydrofuran to the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin is 1mL:100mg;

[0089] (1.6) Add potassium ion selective permeable solution at 1 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a 0.1 mol / L potassium chloride solution for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer;

[0090] (1.7) Casting 0.5 mL of a silk fibroin solution containing sodium ions on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution containing sodium ions is solidified, separating the silicon wafer from the silk fibroin film, cutting out contact sites on the silk fibroin film, and attaching the contact sites to the surface of the device prepared in steps (1.1) to (1.6);

[0091] The gradient heating method is as follows: heating at 40°C for 10 min, 50°C for 10 min, 60°C for 10 min and 70°C for 10 min in sequence;

[0092] (1.8) Spin-coat a 2% by mass tannic acid aqueous solution onto the surface of the silk fibroin film in step (1.7) and place at room temperature for 6 hours to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0093] like Figure 2 As shown, the thickness of the silk fibroin substrate 6 is 20 μm, the thickness of the PEDOT:PSS / CNFs conductive layer 4 is 10 μm, the thickness of the ion selective membrane 7 is 10 μm, and the thickness of the silk fibroin encapsulation layer 8 is 20 μm;

[0094] (2) Preparation of reference electrode;

[0095] (2.1) First, the silk cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution is obtained;

[0096] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 7wt%, and the concentration of sodium ions is 3.5wt%;

[0097] (2.2) The Ag / AgCl mixed paste (mass ratio of Ag to AgCl is 1:1) is printed onto the silk fibroin substrate by screen printing technology, and after being applied twice continuously, the mixture is cured at 60°C for 3 h to form an Ag / AgCl conductive layer on the silk fibroin substrate;

[0098] (2.3) PVB powder was dissolved in methanol solution and mechanically stirred at 300 rpm for 120 minutes. After the solution was completely dissolved, sodium chloride and silver nitrate were added to the PVB solution and mechanically stirred at 500 rpm for 30 minutes to prepare Ag. + The white suspension is the PVB film precursor solution;

[0099] The mass ratio of methanol to PVB is 9:1; the dosage ratio of PVB solution, sodium chloride and silver nitrate is 1 ml:50 mg:50 mg;

[0100] (2.4) PVB film precursor solution was diluted to 1 μL / mm 2 It is drop-coated on the contact site surface of the Ag / AgCl conductive layer and left for 24 hours to allow the solvent to completely evaporate, thus forming a PVB film on the surface of the Ag / AgCl conductive layer.

[0101] (2.5) Casting 0.5 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared in steps (2.1) to (2.5);

[0102] The gradient heating method is as follows: heating at 40°C for 10 min, 50°C for 10 min, 60°C for 10 min and 70°C for 10 min in sequence;

[0103] (2.6) Spin-coating a 2% by mass tannic acid aqueous solution on the surface of the silk fibroin film in step (7) and leaving it at room temperature for 6 hours to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0104] like Figure 3 As shown, the thickness of the silk fibroin substrate 6 is 20 μm, the thickness of the Ag / AgCl conductive layer 5 is 20 μm, the thickness of the PVB film 9 is 10 μm; the thickness of the silk fibroin encapsulation layer 8 is 20 μm;

[0105] (3) Preparation of conventional electrodes;

[0106] like Figure 4 As shown, the preparation of conventional electrodes and ion-selective electrodes is basically the same, the only difference is that the operation of step (1.6) is omitted, that is, the conventional electrode does not have an ion-selective membrane;

[0107] (4) If Figure 1 As shown, through the above steps, the ion selective electrode 2, the reference electrode 3 and the conventional electrode 1 are all integrated onto a silk fibroin substrate, and all except the contact sites are encapsulated by a silk fibroin film, thereby finally forming a silk fibroin-based flexible neural electrode device.

[0108] In the final silk fibroin-based flexible neural electrode device, the Young's modulus of the silk fibroin film is 9.7MPa; the electrochemical impedance of the silk fibroin-based flexible neural electrode device at a frequency of 1Hz is 100Ω, and the long-term stability is 6 days.

[0109] like Fig. 9 , Fig.10 Shown are the sensitivity curve and calibration curve of the potassium ion selective electrode, respectively. The concentrations of potassium chloride solution corresponding to each step in the sensitivity curve are 0.05 mM, 0.125 mM, 0.25 mM, 0.5 mM, 1 mM, 2.5 mM, 10 mM, 25 mM, 50 mM, and 100 mM, respectively. Calculated from the calibration curve, the sensitivity of the potassium ion electrode on the first day was 48.66 mV / dec, and the relative standard deviation (RSD) was 4.98%.

[0110] like Figure 6 The working principle of the ion selective electrode is shown. In the ion selective film, the specific ion selective carrier (such as valinomycin in the potassium ion selective film) has the function of specifically adsorbing and transporting ions (such as potassium ions) and can transport them to the solid transduction layer. When the concentration of specific ions in the measured solution changes, the concentration difference on both sides of the selective film will cause a potential difference. The existence of the potential difference will induce the ions to move into the film and bind to the specific ion transport carrier. After passing through the ion selective film, according to the different transduction mechanisms of the solid transduction layer (i.e., PEDOT:PSS / CNFs layer) (redox reaction mechanism, double layer capacitance mechanism), the ion signal will be converted by the solid transduction layer into an electronic signal and sensed and transmitted, thereby realizing the detection and perception of the specific ion concentration. In the present invention, the PEDOT:PSS / CNFs material can be used as a solid transduction layer and a conductive layer at the same time, converting the ion signal into an electronic signal while completing the transmission of the electronic signal.

[0111] like Fig.18 As shown, the neural electrodes can form conformal contact with the brain model, demonstrating its good flexibility and conformality.

[0112] Comparative Example 1

[0113] A silk fibroin-based flexible neural electrode device for brain-computer interface is basically the same as Example 1, except that the silk fibroin encapsulation layer is not modified with tannic acid.

[0114] The electrochemical impedance of the silk fibroin-based flexible neural electrode device was 100Ω at a frequency of 1Hz, and the sensitivity of the potassium ion selective electrode was 43.68dec / mV on the first day.

[0115] By comparing Comparative Example 1 with Example 1, it can be found that the sensitivity of Comparative Example 1 is reduced. This is because the silk fibroin-based flexible neural electrode device without tannic acid modification has insufficient adhesion to the cerebral cortex, resulting in relatively easy movement or slippage between the electrode and the cortex during testing; this process may cause a water layer to form between the ion-selective membrane and the conductive layer, thereby affecting ion-electron transduction and signal transmission.

[0116] Comparative Example 2

[0117] A silk fibroin-based flexible neural electrode device for brain-computer interface is basically the same as Example 1, except that the gradient heating method is changed to a constant temperature heating method, i.e., heating at 60°C for 40 minutes.

[0118] The Young's modulus of the silk fibroin film is 17MPa; the electrochemical impedance of the silk fibroin-based flexible neural electrode device is 100Ω at a frequency of 1Hz, and the sensitivity of the potassium ion selective electrode on the first day is 47.6dec / mV.

[0119] like Figure 7 , 8 As shown, by comparing Comparative Example 2 with Example 1, it can be found that the Young's modulus of the silk fibroin film of Comparative Example 2 is increased and the flexibility is deteriorated. This is because when the silk fibroin solution is directly heated at a "high temperature" continuously, the molecular chains of the silk fibroin will move violently quickly, and it is easy to form a large number of β-folded structures in a short time, so that the film has strong rigidity. However, during the gradient heating process, the molecular chains of the silk fibroin will move and rearrange relatively gently during the early "low temperature" heating, and then the β-folded structure can be formed relatively slowly. In addition, it can be foreseen that due to the volatilization of part of the solvent during the early "low temperature" heating and the formation of part of the β-folded structure in the system, the molecular chain movement during the later "high temperature" heating will be hindered to a certain extent, thus causing the crystalline structure content formed during the gradient heating process to be lower than the direct "high temperature" heating. In addition, the distribution of the β-folded structure formed during the gradient heating process will also be more uniform, thereby comprehensively ensuring that the gradient heating silk fibroin film has better flexibility and structural stability.

[0120] Comparative Example 3

[0121] A silk fibroin-based flexible neural electrode device for brain-computer interface is basically the same as Example 1, except that in step (4), the silk fibroin solution is not cast on a silicon wafer, but a silk fibroin substrate is directly formed first, and then a PEDOT:PSS / CNFs conductive layer is coated on the silk fibroin substrate.

[0122] The long-term stability of silk fibroin-based neural devices is 3h.

[0123] By comparing Comparative Example 3 with Example 1, it can be found that Comparative Example 3 has low long-term stability and the conductive layer is easily peeled off from the silk fibroin film. This is because the molecular chains inside the silk fibroin film formed earlier have been solidified and cannot move the chain segments. When the PEDOT:PSS / CNFs conductive layer is printed onto the film, PEDOT:PSS cannot form an intercalation structure with the silk fibroin molecular chains.

[0124] Example 2

[0125] A silk fibroin-based flexible neural electrode device for brain-computer interface, the preparation steps of which are as follows:

[0126] (1) Preparation of ion selective electrodes;

[0127] (1.1) First, the silk cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0128] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 7.6wt%, and the concentration of sodium ions is 3.6wt%;

[0129] (1.2) PEDOT:PSS solution with a concentration of 12 mg / mL was mixed with CNFs at a ratio of 1 mL:3 g, and then mechanically stirred at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution;

[0130] (1.3) Printing the PEDOT:PSS / CNFs mixture onto a silicon wafer using a piezoelectric drop-on-demand inkjet printing technique to obtain a silicon wafer with a PEDOT:PSS / CNFs pattern printed thereon;

[0131] Among them, the inkjet piezoelectric drop-on-demand inkjet printing technology uses a sinusoidal piezoelectric pulse with a vibration frequency of 250Hz, an amplitude of 30V, and a pulse period of 20s; the heating temperature of the substrate during printing is 35°C; the nozzle diameter used for printing is 80μm;

[0132] (1.4) 0.6 mL of a silk fibroin solution containing sodium ions was cast onto a silicon wafer having an inkjet-printed PEDOT:PSS / CNFs pattern by using a tape-casting method, and the silk fibroin solution containing sodium ions was solidified by heating using a gradient heating method; after the silk fibroin solution containing sodium ions was solidified, it was placed at 4°C for 24 h, and then the silicon wafer was detached, thereby forming a PEDOT:PSS / CNFs conductive layer on the silk fibroin substrate; the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer were interlaced and fixed between the silk fibroin molecular chains on the silk fibroin substrate;

[0133] The gradient heating method is as follows: heating at 40°C for 11 min, 50°C for 11 min, 60°C for 9 min, and 70°C for 9 min.

[0134] (1.5) Dissolve polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II in tetrahydrofuran to obtain a calcium ion selective permeable solution with a concentration of 5.3wt%; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II, the proportion of polyvinyl chloride is 64wt%, the proportion of diisooctyl sebacate is 33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 1wt%, and the proportion of calcium ion carrier II is 2wt%; the ratio of tetrahydrofuran to the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II is 1mL:100mg;

[0135] (1.6) Add calcium ion selective permeable solution at 2 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a 0.1 mol / L calcium chloride solution for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer;

[0136] (1.7) Casting 0.6 mL of a silk fibroin solution containing sodium ions on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution containing sodium ions is solidified, separating the silicon wafer from the silk fibroin film, cutting out contact sites on the silk fibroin film, and attaching the contact sites to the surface of the device prepared in steps (1.1) to (1.6);

[0137] The gradient heating method is as follows: heating at 40°C for 11 min, 50°C for 11 min, 60°C for 9 min, and 70°C for 9 min.

[0138] (1.8) Spin-coat a 3% by mass tannic acid aqueous solution onto the surface of the silk fibroin film in step (1.7) and place at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0139] The thickness of the silk fibroin substrate is 25 μm, the thickness of the PEDOT:PSS / CNFs conductive layer is 14 μm, the thickness of the ion selective membrane is 13 μm, and the thickness of the silk fibroin encapsulation layer is 25 μm;

[0140] (2) Preparation of reference electrode;

[0141] (2.1) First, the silk cocoons are boiled and degummed in a 0.5% by mass sodium carbonate solution to obtain degummed silk fibers, and then the degummed silk fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0142] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution containing sodium ions, the concentration of silk fibroin is 7.7wt%, and the concentration of sodium ions is 3.9wt%;

[0143] (2.2) The Ag / AgCl mixed paste (mass ratio of Ag to AgCl is 1:1) is printed onto the silk fibroin substrate by screen printing technology, and after being applied twice continuously, the mixture is cured at 60°C for 3 h to form an Ag / AgCl conductive layer on the silk fibroin substrate;

[0144] (2.3) PVB powder was dissolved in methanol solution and mechanically stirred at 300 rpm for 120 minutes. After the solution was completely dissolved, sodium chloride and silver nitrate were added to the PVB solution and mechanically stirred at 500 rpm for 30 minutes to prepare Ag. + The white suspension is the PVB film precursor solution;

[0145] The mass ratio of methanol to PVB is 9:1; the dosage ratio of PVB solution, sodium chloride and silver nitrate is 1 ml:50 mg:50 mg;

[0146] (2.4) PVB film precursor solution was diluted to 2 μL / mm 2 It is drop-coated on the contact site surface of the Ag / AgCl conductive layer and left for 24 hours to allow the solvent to completely evaporate, thus forming a PVB film on the surface of the Ag / AgCl conductive layer.

[0147] (2.5) Casting 0.6 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared in steps (2.1) to (2.5);

[0148] The gradient heating method is as follows: heating at 40°C for 11 min, 50°C for 11 min, 60°C for 9 min, and 70°C for 9 min.

[0149] (2.6) Spin-coating a 6% by mass tannic acid aqueous solution on the surface of the silk fibroin film in step (7) and leaving it at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0150] The thickness of the Ag / AgCl conductive layer is 21 μm, and the thickness of the PVB film is 12 μm;

[0151] (3) Preparation of conventional electrodes;

[0152] The preparation of conventional electrodes and ion-selective electrodes is basically the same, the only difference is that the operation of step (1.6) is omitted, that is, conventional electrodes do not have ion-selective membranes;

[0153] (4) Through the above steps, the ion-selective electrode, reference electrode and conventional electrode are integrated onto a silk fibroin substrate. Except for the contact sites, all of them are encapsulated by a silk fibroin film, thus finally forming a silk fibroin-based flexible neural electrode device.

[0154] In the final silk fibroin-based flexible neural electrode device, the Young's modulus of the silk fibroin film is 9.5MPa; the electrochemical impedance of the silk fibroin-based flexible neural electrode device is 110Ω at a frequency of 1Hz, and the long-term stability is 6 days.

[0155] like Fig.11 , Fig.12Shown are the sensitivity curve and calibration curve of the calcium ion selective electrode, respectively. The concentrations of calcium chloride solution corresponding to each step in the sensitivity curve are 0.1 mM, 0.25 mM, 0.5 mM, 1 mM, 2 mM, 4 mM, 8mM, 16 mM, 32 mM, and 64 mM, respectively. Calculated from the calibration curve, the sensitivity of the calcium ion electrode on the first day was 23.32 mV / dec, and the relative standard deviation (RSD) was 0.2%.

[0156] Example 3

[0157] A silk fibroin-based flexible neural electrode device for brain-computer interface, the preparation steps of which are as follows:

[0158] (1) Preparation of ion selective electrodes;

[0159] (1.1) First, the silk cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0160] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 7.4wt%, and the concentration of sodium ions is 3.7wt%;

[0161] (1.2) PEDOT:PSS solution with a concentration of 12 mg / ml was mixed with CNFs at a ratio of 1 mL:3 g, and then mechanically stirred at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution;

[0162] (1.3) Printing the PEDOT:PSS / CNFs mixture onto a silicon wafer using a piezoelectric drop-on-demand inkjet printing technique to obtain a silicon wafer with a PEDOT:PSS / CNFs pattern printed thereon;

[0163] Among them, the inkjet piezoelectric drop-on-demand inkjet printing technology uses a sinusoidal piezoelectric pulse with a vibration frequency of 250Hz, an amplitude of 30V, and a pulse period of 20s; the heating temperature of the substrate during printing is 35°C; the nozzle diameter used for printing is 80μm;

[0164] (1.4) 0.7 mL of silk fibroin solution was cast onto a silicon wafer with an inkjet-printed PEDOT:PSS / CNFs pattern by a casting method, and the silk fibroin solution was solidified by heating with a gradient heating method; after the silk fibroin solution was solidified, it was placed at 4°C for 24 h, and then the silicon wafer was detached, thereby forming a PEDOT:PSS / CNFs conductive layer on the silk fibroin substrate; the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer were interlaced and fixed between the silk fibroin molecular chains on the silk fibroin substrate;

[0165] The gradient heating method is as follows: heating at 40°C for 12 min, 50°C for 12 min, 60°C for 8 min, and 70°C for 5 min.

[0166] (1.5) polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X are dissolved in tetrahydrofuran to obtain a sodium ion selective permeable solution with a concentration of 5.3 wt%; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X, the proportion of polyvinyl chloride is 66 wt%, the proportion of diisooctyl sebacate is 32 wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.75 wt%, and the proportion of sodium ion carrier X is 1.25 wt%; the ratio of tetrahydrofuran to the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X is 1 mL:100 mg;

[0167] (1.6) Mix the sodium ion selective permeable solution at 3 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a 0.1 mol / L sodium chloride solution for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer;

[0168] (1.7) Casting 0.7 mL of a silk fibroin solution containing sodium ions on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution containing sodium ions is solidified, separating the silicon wafer from the silk fibroin film, cutting out contact sites on the silk fibroin film, and attaching the contact sites to the surface of the device prepared by steps (1.1) to (1.6);

[0169] The gradient heating method is as follows: heating at 40°C for 12 min, 50°C for 12 min, 60°C for 8 min, and 70°C for 5 min.

[0170] (1.8) Spin-coat a 4% by mass tannic acid aqueous solution onto the surface of the silk fibroin film in step (1.7) and place at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0171] The thickness of the silk fibroin substrate is 27 μm, the thickness of the PEDOT:PSS / CNFs conductive layer is 14 μm, the thickness of the ion selective membrane is 14 μm, and the thickness of the silk fibroin encapsulation layer is 27 μm;

[0172] (2) Preparation of reference electrode;

[0173] (2.1) First, the silk cocoons are boiled and degummed in a 0.5% by mass sodium carbonate solution to obtain degummed silk fibers, and then the degummed silk fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0174] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 7.4wt%, and the concentration of sodium ions is 3.7wt%;

[0175] (2.2) The Ag / AgCl mixed paste (mass ratio of Ag to AgCl is 1:1) is printed onto the silk fibroin substrate by screen printing technology, and after being applied twice continuously, the mixture is cured at 60°C for 3 h to form an Ag / AgCl conductive layer on the silk fibroin substrate;

[0176] (2.3) PVB powder was dissolved in methanol solution and mechanically stirred at 300 rpm for 120 minutes. After the solution was completely dissolved, sodium chloride and silver nitrate were added to the PVB solution and mechanically stirred at 500 rpm for 30 minutes to prepare Ag. + The white suspension is the PVB film precursor solution;

[0177] The mass ratio of methanol to PVB is 9:1; the dosage ratio of PVB solution, sodium chloride and silver nitrate is 1 ml:50 mg:50 mg;

[0178] (2.4) PVB film precursor solution was diluted to 3 μL / mm 2 It is drop-coated on the contact site surface of the Ag / AgCl conductive layer and left for 24 hours to allow the solvent to completely evaporate, thus forming a PVB film on the surface of the Ag / AgCl conductive layer.

[0179] (2.5) Casting 0.7 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared in steps (2.1) to (2.5);

[0180] The gradient heating method is as follows: heating at 40°C for 12 min, 50°C for 12 min, 60°C for 8 min, and 70°C for 5 min.

[0181] (2.6) Spin-coating a 4% by mass tannic acid aqueous solution on the surface of the silk fibroin film in step (7) and leaving it at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0182] The thickness of the Ag / AgCl conductive layer is 22 μm, and the thickness of the PVB film is 14 μm;

[0183] (3) Preparation of conventional electrodes;

[0184] The preparation of conventional electrodes and ion-selective electrodes is basically the same, the only difference is that the operation of step (1.6) is omitted, that is, conventional electrodes do not have ion-selective membranes;

[0185] (4) Through the above steps, the ion-selective electrode, reference electrode and conventional electrode are integrated onto a silk fibroin substrate. Except for the contact sites, all of them are encapsulated by a silk fibroin film, thus finally forming a silk fibroin-based flexible neural electrode device.

[0186] In the final silk fibroin-based flexible neural electrode device, the Young's modulus of the silk fibroin film is 9.1MPa; the electrochemical impedance of the silk fibroin-based flexible neural electrode device at a frequency of 1Hz is 130Ω, and the long-term stability is 6 days.

[0187] like Fig.13 , Fig.14 Shown are the sensitivity curve and calibration curve of the sodium ion selective electrode. The concentrations of sodium chloride solution corresponding to each step in the sensitivity curve are 0.5 mM, 1 mM, 3 mM, 6 mM, 12.5 mM, 2.5 mM, 5 mM, and 10 mM, respectively. Calculated from the calibration curve, the sensitivity of the sodium ion electrode on the first day was 39.7 mV / dec, and the relative standard deviation (RSD) was 4.37%.

[0188] like Figures 15-17 The long-term stability of the potassium ion selective electrode, calcium ion selective electrode, and sodium ion selective electrode are shown respectively; the sensitivity of the three ion selective electrodes remains almost unchanged within a week.

[0189] Example 4

[0190] A silk fibroin-based flexible neural electrode device for brain-computer interface, the preparation steps of which are as follows:

[0191] (1) Preparation of ion selective electrodes;

[0192] (1.1) First, the silk cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0193] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 8wt%, and the concentration of sodium ions is 3.8wt%;

[0194] (1.2) PEDOT:PSS solution with a concentration of 12 mg / ml was mixed with CNFs at a ratio of 1 mL:3 g, and then mechanically stirred at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution;

[0195] (1.3) Printing the PEDOT:PSS / CNFs mixture onto a silicon wafer using a piezoelectric drop-on-demand inkjet printing technique to obtain a silicon wafer with a PEDOT:PSS / CNFs pattern printed thereon;

[0196] Among them, the inkjet piezoelectric drop-on-demand inkjet printing technology uses a sinusoidal piezoelectric pulse with a vibration frequency of 250Hz, an amplitude of 30V, and a pulse period of 20s; the heating temperature of the substrate during printing is 35°C; the nozzle diameter used for printing is 80μm;

[0197] (1.4) 0.8 mL of silk fibroin solution was cast on a silicon wafer with an inkjet-printed PEDOT:PSS / CNFs pattern by a casting method, and the silk fibroin solution was solidified by heating with a gradient heating method; after the silk fibroin solution was solidified, it was placed at 4°C for 24 h, and then the silicon wafer was detached, i.e., a PEDOT:PSS / CNFs conductive layer was formed on the silk fibroin substrate; the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer were interlaced and fixed between the silk fibroin molecular chains on the silk fibroin substrate;

[0198] The gradient heating method is as follows: heating at 40°C for 13 min, 50°C for 12 min, 60°C for 5 min, and 70°C for 8 min.

[0199] (1.5) Dissolve polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin in tetrahydrofuran to obtain a potassium ion selective permeable solution with a concentration of 5.3wt%; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin, the proportion of polyvinyl chloride is 65wt%, the proportion of diisooctyl sebacate is 33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5wt%, and the proportion of valinomycin is 1.5wt%; the ratio of tetrahydrofuran to the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin is 1mL:100mg;

[0200] (1.6) Add potassium ion selective permeable solution at 4 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a 0.1 mol / L potassium chloride solution for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer;

[0201] (1.7) Casting 0.8 mL of a silk fibroin solution containing sodium ions on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution containing sodium ions is solidified, separating the silicon wafer from the silk fibroin film, cutting out contact sites on the silk fibroin film, and attaching the contact sites to the surface of the device prepared in steps (1.1) to (1.6);

[0202] The gradient heating method is as follows: heating at 40°C for 13 min, 50°C for 12 min, 60°C for 5 min, and 70°C for 8 min.

[0203] (1.8) Spin-coat a 6% by mass tannic acid aqueous solution onto the surface of the silk fibroin film in step (1.7) and place at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0204] The thickness of the silk fibroin substrate is 35 μm, the thickness of the PEDOT:PSS / CNFs conductive layer is 16 μm, the thickness of the ion selective membrane is 16 μm, and the thickness of the silk fibroin encapsulation layer is 35 μm;

[0205] (2) Preparation of reference electrode;

[0206] (2.1) First, the silk cocoons are boiled and degummed in a 0.5% by mass sodium carbonate solution to obtain degummed silk fibers, and then the degummed silk fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0207] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution containing sodium ions, the concentration of silk fibroin is 8wt%, and the concentration of sodium ions is 3.8wt%;

[0208] (2.2) The Ag / AgCl mixed paste (mass ratio of Ag to AgCl is 1:1) is printed onto the silk fibroin substrate by screen printing technology, and after being applied four times continuously, it is cured at 60°C for 3 h to form an Ag / AgCl conductive layer on the silk fibroin substrate;

[0209] (2.3) PVB powder was dissolved in methanol solution and mechanically stirred at 300 rpm for 120 minutes. After the solution was completely dissolved, sodium chloride and silver nitrate were added to the PVB solution and mechanically stirred at 500 rpm for 30 minutes to prepare Ag. + The white suspension is the PVB film precursor solution;

[0210] The mass ratio of methanol to PVB is 9:1; the dosage ratio of PVB solution, sodium chloride and silver nitrate is 1 ml:50 mg:50 mg;

[0211] (2.4) PVB film precursor solution was prepared at 4 μL / mm 2 It is drop-coated on the contact site surface of the Ag / AgCl conductive layer and left for 24 hours to allow the solvent to completely evaporate, thus forming a PVB film on the surface of the Ag / AgCl conductive layer.

[0212] (2.5) Casting 0.8 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution containing sodium ions is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared in steps (2.1) to (2.5);

[0213] The gradient heating method is as follows: heating at 40°C for 13 min, 50°C for 12 min, 60°C for 5 min, and 70°C for 8 min.

[0214] (2.6) Spin-coating a 6% by mass tannic acid aqueous solution on the surface of the silk fibroin film in step (7) and leaving it at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0215] The thickness of the Ag / AgCl conductive layer is 35 μm, and the thickness of the PVB film is 15 μm;

[0216] (3) Preparation of conventional electrodes;

[0217] The preparation of conventional electrodes and ion-selective electrodes is basically the same, the only difference is that the operation of step (1.6) is omitted, that is, conventional electrodes do not have ion-selective membranes;

[0218] (4) Through the above steps, the ion-selective electrode, reference electrode and conventional electrode are integrated onto a silk fibroin substrate. Except for the contact sites, all of them are encapsulated by a silk fibroin film, thus finally forming a silk fibroin-based flexible neural electrode device.

[0219] In the final silk fibroin-based flexible neural electrode device, the Young's modulus of the silk fibroin film was 9.4MPa; the electrochemical impedance of the silk fibroin-based flexible neural electrode device was 150Ω at a frequency of 1Hz, and the long-term stability was 6 days; the sensitivity of the potassium ion selective electrode on the first day was 43.68dec / mV.

[0220] Example 5

[0221] A silk fibroin-based flexible neural electrode device for brain-computer interface, the preparation steps of which are as follows:

[0222] (1) Preparation of ion selective electrodes;

[0223] (1.1) First, the silk cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0224] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution containing sodium ions, the concentration of silk fibroin is 7.2wt%, and the concentration of sodium ions is 3.9wt%;

[0225] (1.2) PEDOT:PSS solution with a concentration of 12 mg / mL was mixed with CNFs at a ratio of 1 mL:3 g, and then mechanically stirred at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution;

[0226] (1.3) Printing the PEDOT:PSS / CNFs mixture onto a silicon wafer using a piezoelectric drop-on-demand inkjet printing technique to obtain a silicon wafer with a PEDOT:PSS / CNFs pattern printed thereon;

[0227] Among them, the inkjet piezoelectric drop-on-demand inkjet printing technology uses a sinusoidal piezoelectric pulse with a vibration frequency of 250Hz, an amplitude of 30V, and a pulse period of 20s; the heating temperature of the substrate during printing is 35°C; the nozzle diameter used for printing is 80μm;

[0228] (1.4) 0.9 mL of silk fibroin solution was cast on a silicon wafer with an inkjet-printed PEDOT:PSS / CNFs pattern by a casting method, and the silk fibroin solution was solidified by heating with a gradient heating method; after the silk fibroin solution was solidified, it was placed at 4°C for 24 hours, and then the silicon wafer was detached, i.e., a PEDOT:PSS / CNFs conductive layer was formed on the silk fibroin substrate; the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer were interlaced and fixed between the silk fibroin molecular chains on the silk fibroin substrate;

[0229] The gradient heating method is as follows: heating at 40°C for 14 min, 50°C for 15 min, 60°C for 6 min, and 70°C for 5 min.

[0230] (1.5) Dissolve polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II in tetrahydrofuran to obtain a calcium ion selective permeable solution with a concentration of 5.3wt%; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II, the proportion of polyvinyl chloride is 64.5wt%, the proportion of diisooctyl sebacate is 33.5wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5wt%, and the proportion of calcium ion carrier II is 1.5wt%; the ratio of tetrahydrofuran to the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II is 1mL:100mg;

[0231] (1.6) Add calcium ion selective permeable solution at 5 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a 0.1 mol / L calcium chloride solution for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer;

[0232] (1.7) Casting 0.9 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared by steps (1.1) to (1.6);

[0233] The gradient heating method is as follows: heating at 40°C for 14 min, 50°C for 15 min, 60°C for 6 min, and 70°C for 5 min.

[0234] (1.8) Spin-coat a 7% by mass tannic acid aqueous solution onto the surface of the silk fibroin film in step (1.7) and place at room temperature for 6 hours to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0235] The thickness of the silk fibroin substrate is 35 μm, the thickness of the PEDOT:PSS / CNFs conductive layer is 17 μm, the thickness of the ion selective membrane is 19 μm, and the thickness of the silk fibroin encapsulation layer is 35 μm;

[0236] (2) Preparation of reference electrode;

[0237] (2.1) First, the silk cocoons are boiled and degummed in a 0.5% by mass sodium carbonate solution to obtain degummed silk fibers, and then the degummed silk fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0238] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 7.2wt%, and the concentration of sodium ions is 3.9wt%;

[0239] (2.2) The Ag / AgCl mixed paste (mass ratio of Ag to AgCl is 1:1) is printed onto the silk fibroin substrate by screen printing technology, and after being applied three times continuously, the mixture is cured at 60°C for 3 h to form an Ag / AgCl conductive layer on the silk fibroin substrate;

[0240] (2.3) PVB powder was dissolved in methanol solution and mechanically stirred at 300 rpm for 120 minutes. After the solution was completely dissolved, sodium chloride and silver nitrate were added to the PVB solution and mechanically stirred at 500 rpm for 30 minutes to prepare Ag. + The white suspension is the PVB film precursor solution;

[0241] The mass ratio of methanol to PVB is 9:1; the dosage ratio of PVB solution, sodium chloride and silver nitrate is 1 ml:50 mg:50 mg;

[0242] (2.4) PVB film precursor solution was diluted to 5 μL / mm 2 It is drop-coated on the contact site surface of the Ag / AgCl conductive layer and left for 24 hours to allow the solvent to completely evaporate, thus forming a PVB film on the surface of the Ag / AgCl conductive layer.

[0243] (2.5) Casting 0.9 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution containing sodium ions is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared in steps (2.1) to (2.5);

[0244] The gradient heating method is as follows: heating at 40°C for 14 min, 50°C for 15 min, 60°C for 6 min, and 70°C for 5 min.

[0245] (2.6) Spin-coating a 7% by mass tannic acid aqueous solution on the surface of the silk fibroin film in step (7) and leaving it at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0246] The thickness of the Ag / AgCl conductive layer is 38 μm, and the thickness of the PVB film is 17 μm;

[0247] (3) Preparation of conventional electrodes;

[0248] The preparation of conventional electrodes and ion-selective electrodes is basically the same, the only difference is that the operation of step (1.6) is omitted, that is, conventional electrodes do not have ion-selective membranes;

[0249] (4) Through the above steps, the ion-selective electrode, reference electrode and conventional electrode are integrated onto a silk fibroin substrate. Except for the contact sites, all of them are encapsulated by a silk fibroin film, thus finally forming a silk fibroin-based flexible neural electrode device.

[0250] In the final silk fibroin-based flexible neural electrode device, the Young's modulus of the silk fibroin film was 9.1MPa; the electrochemical impedance of the silk fibroin-based flexible neural electrode device was 170Ω at a frequency of 1Hz, and the long-term stability was 6 days; the sensitivity of the calcium ion selective electrode on the first day was 22.3dec / mV.

[0251] Example 6

[0252] A silk fibroin-based flexible neural electrode device for brain-computer interface, the preparation steps of which are as follows:

[0253] (1) Preparation of ion selective electrodes;

[0254] (1.1) First, the silk cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, and then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0255] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 7.8wt%, and the concentration of sodium ions is 4wt%;

[0256] (1.2) PEDOT:PSS solution with a concentration of 12 mg / mL was mixed with CNFs at a ratio of 1 mL:3 g, and then mechanically stirred at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution;

[0257] (1.3) Printing the PEDOT:PSS / CNFs mixture onto a silicon wafer using a piezoelectric drop-on-demand inkjet printing technique to obtain a silicon wafer with a PEDOT:PSS / CNFs pattern printed thereon;

[0258] Among them, the inkjet piezoelectric drop-on-demand inkjet printing technology uses a sinusoidal piezoelectric pulse with a vibration frequency of 250Hz, an amplitude of 30V, and a pulse period of 20s; the heating temperature of the substrate during printing is 35°C; the nozzle diameter used for printing is 80μm;

[0259] (1.4) 1 mL of silk fibroin solution was cast onto a silicon wafer with an inkjet-printed PEDOT:PSS / CNFs pattern by a tape-casting method, and the silk fibroin solution containing sodium ions was solidified by heating using a gradient heating method; after the silk fibroin solution was solidified, it was placed at 4°C for 24 h, and then the silicon wafer was detached, thereby forming a PEDOT:PSS / CNFs conductive layer on the silk fibroin substrate; the PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer were interlaced and fixed between the silk fibroin molecular chains on the silk fibroin substrate;

[0260] The gradient heating method is as follows: heating at 40°C for 15 min, 50°C for 13 min, 60°C for 6 min, and 70°C for 10 min.

[0261] (1.5) polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X are dissolved in tetrahydrofuran to obtain a sodium ion selective permeable solution with a concentration of 5.3 wt%; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X, the proportion of polyvinyl chloride is 65.5 wt%, the proportion of diisooctyl sebacate is 33 wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5 wt%, and the proportion of sodium ion carrier X is 1 wt%; the ratio of tetrahydrofuran to the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X is 1 mL:100 mg;

[0262] (1.6) Mix the sodium ion selective permeable solution at 6 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a 0.1 mol / L sodium chloride solution for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer;

[0263] (1.7) Casting 1 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared by steps (1.1) to (1.6);

[0264] The gradient heating method is as follows: heating at 40°C for 15 min, 50°C for 13 min, 60°C for 6 min, and 70°C for 10 min.

[0265] (1.8) Spin-coat an 8% by mass tannic acid aqueous solution onto the surface of the silk fibroin film in step (1.7) and place at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0266] The thickness of the silk fibroin substrate is 40 μm, the thickness of the PEDOT:PSS / CNFs conductive layer is 20 μm, the thickness of the ion selective membrane is 20 μm, and the thickness of the silk fibroin encapsulation layer is 40 μm;

[0267] (2) Preparation of reference electrode;

[0268] (2.1) First, the silk cocoons are boiled and degummed in a 0.5% by mass sodium carbonate solution to obtain degummed silk fibers, and then the degummed silk fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained;

[0269] The ratio of formic acid / calcium chloride mixture to degummed silk fiber is 12mL:1g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution containing sodium ions, the concentration of silk fibroin is 7.8wt%, and the concentration of sodium ions is 4wt%;

[0270] (2.2) The Ag / AgCl mixed paste (mass ratio of Ag to AgCl is 1:1) is printed onto the silk fibroin substrate by screen printing technology, and after being applied four times continuously, it is cured at 60°C for 3 h to form an Ag / AgCl conductive layer on the silk fibroin substrate;

[0271] (2.3) PVB powder was dissolved in methanol solution and mechanically stirred at 300 rpm for 120 minutes. After the solution was completely dissolved, sodium chloride and silver nitrate were added to the PVB solution and mechanically stirred at 500 rpm for 30 minutes to prepare Ag. + The white suspension is the PVB film precursor solution;

[0272] The mass ratio of methanol to PVB is 9:1; the dosage ratio of PVB solution, sodium chloride and silver nitrate is 1 ml:50 mg:50 mg;

[0273] (2.4) PVB film precursor solution was prepared at 6 μL / mm 2 It is drop-coated on the contact site surface of the Ag / AgCl conductive layer and left for 24 hours to allow the solvent to completely evaporate, thus forming a PVB film on the surface of the Ag / AgCl conductive layer.

[0274] (2.5) Casting 1 mL of silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared in steps (2.1) to (2.5);

[0275] The gradient heating method is as follows: heating at 40°C for 15 min, 50°C for 13 min, 60°C for 6 min, and 70°C for 10 min.

[0276] (2.6) Spin-coating an 8% by mass tannic acid aqueous solution on the surface of the silk fibroin film in step (7) and leaving it at room temperature for 6 h to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer;

[0277] The thickness of the Ag / AgCl conductive layer is 40 μm, and the thickness of the PVB film is 20 μm;

[0278] (3) Preparation of conventional electrodes;

[0279] The preparation of conventional electrodes and ion-selective electrodes is basically the same, the only difference is that the operation of step (1.6) is omitted, that is, conventional electrodes do not have ion-selective membranes;

[0280] (4) Through the above steps, the ion-selective electrode, reference electrode and conventional electrode are integrated onto a silk fibroin substrate. Except for the contact sites, all of them are encapsulated by a silk fibroin film, thus finally forming a silk fibroin-based flexible neural electrode device.

[0281] In the final silk fibroin-based flexible neural electrode device, the Young's modulus of the silk fibroin film is 9.9MPa; the electrochemical impedance of the silk fibroin-based flexible neural electrode device at a frequency of 1Hz is 200Ω, and the long-term stability is 6 days; the sensitivity of the sodium ion selective electrode on the first day is 43.68dec / mV.

Claims

1. A silk fibroin-based flexible neural electrode device for brain-computer interface, wherein an ion-selective electrode and a reference electrode are integrated on the silk fibroin-based flexible neural electrode device, characterized in that: The ion selective electrode comprises a silk fibroin substrate, a PEDOT:PSS / CNFs conductive layer, an ion selective membrane and a silk fibroin encapsulation layer, wherein the silk fibroin substrate, the PEDOT:PSS / CNFs conductive layer and the ion selective membrane are arranged from bottom to top; The PEDOT:PSS molecular chains in the PEDOT:PSS / CNFs conductive layer are interspersed and fixed between the silk fibroin molecular chains on the silk fibroin substrate; The reference electrode includes a silk fibroin substrate, an Ag / AgCl conductive layer, a PVB film and a silk fibroin encapsulation layer, and the silk fibroin substrate, the Ag / AgCl conductive layer and the PVB film are arranged from bottom to top; The silk fibroin substrate is a silk fibroin film, and the silk fibroin encapsulation layer is a tannic acid-modified silk fibroin film; The Young's modulus of silk fibroin film is below 10 MPa; The preparation steps of ion selective electrodes are as follows: (1) firstly, the silkworm cocoons are boiled and degummed in a sodium carbonate solution with a mass fraction of 0.5% to obtain degummed silk fibroin fibers, then the degummed silk fibroin fibers are dissolved in a formic acid / calcium chloride mixed solution to obtain a silk fibroin solution containing calcium ions, and finally a saturated sodium sulfate solution is added to the silk fibroin solution containing calcium ions, and after centrifugal filtration, a silk fibroin solution containing sodium ions is obtained; (2) After mixing the PEDOT:PSS solution with CNFs, the mixture was mechanically stirred at 300 rpm for 20 min to obtain a uniformly dispersed PEDOT:PSS / CNFs mixed solution; (3) using piezoelectric drop-on-demand inkjet printing technology to print the PEDOT:PSS / CNFs mixed solution onto a silicon wafer to obtain a silicon wafer with an inkjet-printed PEDOT:PSS / CNFs pattern; (4) 0.5-1 mL of silk fibroin solution was cast on a silicon wafer with an inkjet-printed PEDOT:PSS / CNFs pattern by a tape casting method, and the silk fibroin solution was solidified by heating with a gradient heating method; after the silk fibroin solution containing sodium ions was solidified, it was placed at 4°C for 24 hours, and then the silicon wafer was detached, thus forming a PEDOT:PSS / CNFs conductive layer on the silk fibroin substrate; (5) The ion selective precursor solution is adjusted to 1-6 μL / mm 2 Apply it on the contact site surface of the PEDOT:PSS / CNFs conductive layer, leave it for 24 hours to allow the solvent to completely evaporate, and then soak it in a target ion solution with a concentration of 0.1 mol / L for 24 hours to form an ion selective membrane on the surface of the PEDOT:PSS / CNFs conductive layer; (6) casting 0.5-1 mL of the silk fibroin solution on a silicon wafer by a tape casting method, and heating the silk fibroin solution by a gradient heating method to solidify the silk fibroin solution; after the silk fibroin solution containing sodium ions is solidified, the silicon wafer and the silk fibroin film are separated, and the contact sites are cut out on the silk fibroin film, and the contact sites are attached to the surface of the device prepared in steps (1) to (5); (7) Spin-coat a tannic acid solution with a mass fraction of 2 to 8% onto the surface of the silk fibroin film in step (6), and place at room temperature for 6 hours to allow cross-linking to occur, thereby forming a silk fibroin encapsulation layer.

2. The silk fibroin-based flexible neural electrode device for brain-computer interface according to claim 1, characterized in that: The thickness of the silk fibroin substrate in the ion selective electrode and the reference electrode is 20-40 μm, the thickness of the PEDOT:PSS / CNFs conductive layer is 10-20 μm, the thickness of the ion selective membrane is 10-20 μm, and the thickness of the Ag / AgCl conductive layer is 20-40 μm. The thickness of the PVB film is 10-20 μm, and the thickness of the silk fibroin encapsulation layer is 20-40 μm.

3. The silk fibroin-based flexible neural electrode device for brain-computer interface according to claim 1, characterized in that: In step (1), the ratio of the formic acid / calcium chloride mixture to the degummed silk fiber is 12 mL: 1 g; in the formic acid / calcium chloride mixture, the mass proportion of calcium chloride is 4.5%; in the silk fibroin solution, the concentration of silk fibroin is 7-8 wt%, and the sodium ion concentration is 3.5-4 wt%.

4. The silk fibroin-based flexible neural electrode device for brain-computer interface according to claim 1, characterized in that: In step (2), the ratio of the amount of PEDOT:PSS solution to that of CNFs is 1 mL:3 g, and the concentration of the PEDOT:PSS solution is 12 mg / mL.

5. The silk fibroin-based flexible neural electrode device for brain-computer interface according to claim 1, characterized in that: In step (3), the piezoelectric inkjet on-demand inkjet printing technology uses a sinusoidal piezoelectric pulse with a vibration frequency of 250 Hz, an amplitude of 30 V, and a pulse period of 20 s; the heating temperature of the substrate during printing is 35° C.; and the nozzle diameter used for printing is 80 μm.

6. The silk fibroin-based flexible neural electrode device for brain-computer interface according to claim 1, characterized in that: In step (4) and step (6), the gradient heating method is specifically: heating at 40°C for 10 to 15 min, heating at 50°C for 10 to 15 min, heating at 60°C for 5 to 10 min, and heating at 70°C for 5 to 10 min.

7. The silk fibroin-based flexible neural electrode device for brain-computer interface according to claim 1, characterized in that: In step (5), the ion-selective precursor solution is a potassium ion selective permeable solution, a calcium ion selective permeable solution or a sodium ion selective permeable solution, and the target ion solution is a potassium ion solution, a calcium ion solution or a sodium ion solution; The potassium ion selective permeable solution is obtained by dissolving polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin in tetrahydrofuran; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and valinomycin, the proportion of polyvinyl chloride is 64-66wt%, the proportion of diisooctyl sebacate is 32-33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5-1wt%, and the proportion of valinomycin is 1-2wt%; The calcium ion selective permeable solution is obtained by dissolving polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II in tetrahydrofuran; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and calcium ion carrier II, the proportion of polyvinyl chloride is 64-66wt%, the proportion of diisooctyl sebacate is 32-33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5-1wt%, and the proportion of calcium ion carrier II is 1-2wt%; The sodium ion selective permeable solution is obtained by dissolving polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X in tetrahydrofuran; based on the total amount of polyvinyl chloride, diisooctyl sebacate, sodium 4[3,5-bis(trifluoromethyl)phenyl]borate and sodium ion carrier X, the proportion of polyvinyl chloride is 64-66wt%, the proportion of diisooctyl sebacate is 32-33wt%, the proportion of sodium 4[3,5-bis(trifluoromethyl)phenyl]borate is 0.5-1wt%, and the proportion of sodium ion carrier X is 1-2wt%.

8. The silk fibroin-based flexible neural electrode device for brain-computer interface according to claim 1, characterized in that: Conventional electrodes are also integrated on the silk fibroin-based flexible neural electrode device. The only difference between conventional electrodes and ion-selective electrodes is that they do not have ion-selective membranes.

Citation Information

Patent Citations

  • All-solid-state ion selective electrode, preparation method thereof and application of all-solid-state ion selective electrode in biochemical electrolyte detection

    CN115575466A

  • Preparation method of flexible double-faced full-solid ion concentration detection sensor

    CN102980926A

  • Silk fibroin conductive thin film material and hot-temperature auxiliary stripping process thereof

    CN116589719A